2007
DOI: 10.1021/bi0617613
|View full text |Cite
|
Sign up to set email alerts
|

The GCN4 bZIP Targets Noncognate Gene Regulatory Sequences:  Quantitative Investigation of Binding at Full and Half Sites

Abstract: : We previously reported that a basic region/leucine zipper (bZIP) protein, a hybrid of the GCN4 basic region and C/EBP leucine zipper, not only recognizes cognate target sites AP-1 (5′-TGACTCA-3′) and cAMP-response element (CRE) (5′-TGACGTCA-3′) but also binds selectively to noncognate DNA sites: C/EBP (CCAAT/enhancer binding protein, 5′-TTGCGCAA), XRE1 (xenobiotic response element, 5′-TTGCGTGA), HRE (HIF response element, 5′-GCACGTAG), and E-box (5′-CACGTG). In this work, we used electrophoretic mobility sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
53
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(59 citation statements)
references
References 54 publications
6
53
0
Order By: Relevance
“…We initially observed that the wt bZIP displays significant affinity for the C/EBP site only 100-fold weaker than that at the cognate AP-1 and CRE sites [both sites give a K d of 1.6 × 10 −16 M 2 ; previous data recalculated as dimeric dissociation constants (10)]. In contrast, the affinities at other noncognate sites, including the Arnt E-box site, are reduced ≥2000-fold (Table 1) (9).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We initially observed that the wt bZIP displays significant affinity for the C/EBP site only 100-fold weaker than that at the cognate AP-1 and CRE sites [both sites give a K d of 1.6 × 10 −16 M 2 ; previous data recalculated as dimeric dissociation constants (10)]. In contrast, the affinities at other noncognate sites, including the Arnt E-box site, are reduced ≥2000-fold (Table 1) (9).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the affinities at other noncognate sites, including the Arnt E-box site, are reduced ≥2000-fold (Table 1) (9). Furthermore, the affinity of the wt bZIP at the Arnt E-box site increases ∼30-fold from that at its half-site; likewise, the affinity of the wt bZIP at the AP-1 site increases 44-fold from that at its half-site ( K d = 7.0 × 10 −15 M 2 ) (10). These affinity increases are in agreement with measurements by Hollenbeck and Oakley; the affinity of their GCN4 bZIP derivative at the AP-1 and CRE sites increases 30- and 80-fold, respectively, from that at the TGAC half-site (14).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gcn4 can also bind to naturally occurring variants of this sequence (TGATTCA, TGACTCT, TG ACTGA, TGACTAT, and ATGACTCT), and therefore, using a computer algorithm, this consensus site was generalized to RRR WGASTCA (R ϭ purine, W ϭ T or A, and S ϭ G or C) (9). Gcn4 also binds to GCRE half-sites with high affinity in vitro (15,16).…”
mentioning
confidence: 99%